An influence of carbon matrix origin on electrochemical behaviour of carbon-tin anode nanocomposites. (10th August 2016) - Chojnacka, A.; Świętosławski, M.; Maziarz, W.; Dziembaj, R.; Molenda, M.
Abstract: Electrode materials in which tin nanograins are encapsulated in carbon matrix obtained from different origin (starch or modified polymer) were examined. Morphology of the C/Sn composites was observed using transmission electron microscopy (TEM). Electrochemical impedance spectroscopy (EIS) analysis in different states of charge (SOC) at initial cycle together with a long term galvanostatic charge-discharge cycling tests allowed determining the influence of carbon coating origin on the electrochemical behaviour of C/Sn nanocomposites. X-ray photoelectron spectroscopy (XPS) measurements of C/Sn materials before cycling and after first cycle were performed to observe changes in surface composition of the material which occur during electrochemical reaction. The results of surface characterization as well as electrochemical studies of C/Sn nanocomposites indicated that the origin of carbon precursor has a major impact on the composites' morphology and electrochemical behaviour. Long term galvanostatic charge-discharge cycling tests proved that the carbon obtained from MPNVF precursor allows better encapsulation of tin nanograins in the buffer matrix. Furthermore, according to the XPS studies carbon coating based on MPNVF is more chemically stable versus electrolyte, which contributes directly to the improved protection of active material against physical damage. The charge capacity of MPNVF-based composite was 589 mAh g −1 after 70 cycles, which constitutes 59% of theoretical metallic tin capacity.